Advanced database principles and REST in Grails 3 - Kousen, Ken; Safari eBooks ([Place of publication not identified] : O'Reilly, 2017)
"In this video course, expert Java trainer and consultant Ken Kousen explores advanced database features that include switching databases, using multiple databases in a single Grails application, and how to invoke stored procedures by bypassing Hibernate. He also reveals how to map data to an existing database using Grails 3 custom ORM mapping tags. From there, he dives into a review of REST principles. He builds a RESTful web service using the rest-api profile, adds a RESTful controller, and looks at JSON views. Finally, he shows you how to conduct an integration test using a REST client."--Resource description page.
Presenter, Ken Kousen.
Title from title screen (viewed May 11, 2017).
Keywords: Grails (Computer file); Groovy (Computer program language); Web site development; Application software -- Development; Open source software; Electronic books